Assessing Inequalities in Preventive Care Use in Europe - Vincenzo Carrieri; Ansgar Wübker (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2012)
This paper presents the first cross-country estimation of needs-adjusted income and education-related inequalities in the use of a whole set of preventive care treatments. Analysis is based on the first three waves of the Survey of Health, Ageing and Retirement (SHARE) for individuals aged 50 and over living in 13 European countries. We employ alternative concentration indices based on the CI-corrections for binary outcomes to compute inequalities in the use of breast cancer screening, of colorectal cancer screening, of influenza vaccination, and of routine prevention tests (blood pressure, cholesterol, and blood sugar tests). After controlling for needs, we find that in many European countries strong pro-rich and educational inequalities exist with respect to breast and colon cancer screening, blood tests and flu-vaccination. Furthermore, poor and less educated people are more likely than the better off to use preventive care late, e.g. when health shocks occurred or health problems already display symptoms. Finally, results suggest that access to treatments within a specialist setting is generally less equal than access to treatments provided within a GP setting.
Keywords: I14; D63; 330; preventive care; socio-economic related inequalities; concentration indices